DAMPAK PERANG DAGANG ANTARA AMERIKA SERIKAT-TIONGKOK TERHADAP EKSPOR MINYAK KELAPA SAWIT INDONESIA KE TIONGKOK 2018-2019 - Dita, Delfia Tiara; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research analyzes the impact of the trade war between the United States and Tiongkok on Indonesian palm oil exports to Tiongkok in 2018-2019. In the trade war that occurred between the United States and Tiongkok, Indonesia made several policies to deal with the Trade War on palm oil exports to Tiongkok. This research uses an explanatory qualitative method, and uses a neoliberalism perspective, a theory used by international trade theory and uses a nation state level of analysis, with data collection techniques from primary data and various sources, including media reports and official documents related to the trade war. United States and Tiongkok on palm oil exports. The data obtained was then analyzed to identify the impact of the United States and Tiongkok trade war on Indonesian palm oil exports to Tiongkok. The results of the research show that the trade war between the United States and Tiongkok has an influence on Indonesian palm oil exports to Tiongkok. As the value of Indonesian CPO exports decreased, shares in the agricultural industry sector and CPO producers experienced a significant decline. And Indonesia also provided policies to deal with the trade war that occurred between the United States and Tiongkok regarding Indonesian palm oil exports. Keywords: impact of the Trade War, palm oil exports, CPO dynamics